Preaching and Asceticism: Humility and Chastity in the Sermons for Laity by Caesarius of Arles - Aguirre Durán, Marcelo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
The preaching of Bishop Caesarius of Arles (†542) comprises a set of teachings on Christian moral, doctrine and Holy Scripture, addressed to clerics, monks and lay people of all groups, ages and occupations. This universal character has made his sermons a privileged source of knowledge about a community of the faithful in southern Gaul during the first half of the 6th century. Caesarius’s educational programme for the laity consisted of moral and doctrinal training, accompanied by simple exegesis. His aim was to instruct and convert them to the faith, for he wished to perfect the moral and catechetical conditions of his flock. This article therefore aims to show how the preaching of this Provençal prelate was organised on the basis of monastic asceticism, in order to educate the laity in humility and chastity, so that they could live the values of baptism.